humanized mice for the study of dengue disease pathogenesis: biological assays (2022)
Dengue is one of the most prevalent infectious diseases around the world, present in all continents and mainly affecting developing countries. With few tools to fight and study this disease, it is imperative to have reliable animal models that not only recapitulate human disease but also contain human components to understand the pathogenic mechanism and immune responses, allowing the development of new treatments and vaccines against dengue. Humanized mice are a significant advance in the development of in vivo models to understanding the relation of the human immune system and target organs such as the liver during the infection by dengue virus, allowing basic and preclinical research. In this chapter, we describe the use of humanized NSG mice (huNSG) for the study of dengue disease. The first model describes reconstitution of the human immune system by transplanting human CD34+ stem cells in newborn or adult NSG mice. The second model combines the reconstitution with CD34+ stem cells with the transplant of human primary hepatocytes. This dual reconstituted animal will have two of the major players involved in the development of dengue infection. However, there are still more biological components missing in this model for dengue, but researchers continue working to improve the huNSG model to reconstitute other human components.